2008
DOI: 10.1021/es801907r
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Predictors of Perfluorinated Chemicals: A Study from the Danish National Birth Cohort

Abstract: This study investigated the association between dietary variables and plasma levels of perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) among 1076 pregnant women. Diet was assessed at midpregnancy by a food-frequency questionnaire. Mean first trimester plasma PFOS and PFOA levels were 35.1 and 5.6 ng/mL respectively. PFOS levels were positively associated (p < 0.05) with intake of red meat, animal fats, and snacks (e.g., popcorn, potato chips), whereas intake of vegetables and poultry was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
89
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 31 publications
(53 reference statements)
10
89
3
Order By: Relevance
“…Two previous reports also reported that consumption of fish and shellfish was positively correlated with plasma or serum concentrations of PFOS in Norway 9,31) . In contrast, meat, but not fish, was a significant predictor of PFOS levels in plasma among pregnant Danish women 11) . The high bioaccumulative potential of PFOS in the food web 1) and high intake of seafood in Japan, Spain and Norway may explain these results.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Two previous reports also reported that consumption of fish and shellfish was positively correlated with plasma or serum concentrations of PFOS in Norway 9,31) . In contrast, meat, but not fish, was a significant predictor of PFOS levels in plasma among pregnant Danish women 11) . The high bioaccumulative potential of PFOS in the food web 1) and high intake of seafood in Japan, Spain and Norway may explain these results.…”
Section: Discussionmentioning
confidence: 73%
“…Several reports have indicated that PFOS and PFOA were transferred into the human body mainly through fish intake 9,10) . On the other hand, research in Denmark showed positive associations between concentrations of PFOS in blood and consumption of red meat, animal fat and snacks, but not fish 11) . Few studies have investigated the factors associated with blood levels of PFOS and PFOA in Japan.…”
mentioning
confidence: 93%
“…In a study from Poland, Falandysz et al (2006) showed that individuals who reported a high intake of fish had higher concentrations of PFCs in their blood than those from who did not report high intake of fish. Results from Denmark showed positive associations between PFOS concentrations in serum and consumption of red meat, animal fat and snacks (Halldorsson et al 2008).…”
Section: Human Biomonitoring (Internal Dose)mentioning
confidence: 96%
“…In recent years, the concentrations of PFCs have been extensively measured and studied for human exposure and risk evaluation. Various PFCs have been detected in human blood and milk from North America [6,7], Europe [8,9] and Asia [10,11]. A study shows that both serum albumin proteins and -lactoglobulin proteins had a strong binding affinity for some PFCs [12].…”
mentioning
confidence: 99%
“…In recent years, the levels of PFCs in a series of foodstuffs have been investigated in several countries such as the United Kingdom [15], Canada [13,16], Germany [9] and Spain [14]. Halldorsson et al [6] investigated the correlation between dietary variables and plasma levels of PFOS among 1076 pregnant women. The results show that the PFOS level has positive correlation with intakes of red meat, milk, animal fat, potatoes and snacks without the adjustment analyses for parity, smoking, maternal age, prepregnancy body mass index and socio-occupational status.…”
mentioning
confidence: 99%